KONTRIBUSI SISTEM INFORMASI MANAJEMEN DALAM PENINGKATAN MUTU PENDIDIKAN - Nisa, Kamilatun (Department of Islamic Education Management, 2024)
Education is one of the most crucial aspects of country formation. Management information systems are recognized as a useful instrument for improving educational quality. The purpose of this study is to examine how management information systems can be used to improve educational quality. This study uses three prior publications as references to obtain information on the adoption of management information systems in the educational setting. The research strategy used was an examination of these journals. The findings of this study suggest that implementing management information systems in education still presents hurdles and obstacles. However, in general, the introduction of management information systems in schools has contributed positively to the quality of education.